Association of Cerebral Artery Stenosis With Post-stroke Depression at Discharge and 3 Months After Ischemic Stroke Onset - Qiu, Xiuli; Miao, Jinfeng; Lan, Yan; Sun, Wenzhe; Chen, Yuxi; Cao, Ziqin; Li, Guo; Zhao, Xin; Zhu, Zhou; Zhu, Suiqiang (Frontiers in Psychiatry, 2020)
Background: Post-stroke depression (PSD) is one of the most common complications after stroke, which seriously affects patients' recovery outcome. Although vascular depression has been extensively studied, the relationship between cerebral artery stenosis and PSD has not been clarified so far. Methods: Two hundred ninety-eight patients with ischemic stroke (72 women, 226 men) with computed tomography angiography (CTA) or magnetic resonance angiography (MRA) were included in this study. Cerebral artery stenosis ≥ 50% was used as the cut-off value. The DSM-V diagnostic criteria of PSD was met and the 17-item Hamilton Rating Scale for Depression (HAMD-17) score over 7 at discharge and 3 months after stroke onset was regarded as the primary outcome. The 2 test, Mann-Whitney U test and t test were used to check for statistical significance. Results: At discharge, Barthel index (p＜0.001), left middle cerebral artery stenosis (p = 0.019), drinking history (p = 0.048), basilar artery stenosis (p = 0.037) were significantly associated with PSD. At 3 months after ischemic stroke onset, Barthel index (p = 0.011), left middle cerebral artery stenosis (p = 0.012), female gender (p = 0.001) were significantly associated with PSD. Conclusions: The findings demonstrated that left middle cerebral artery and basilar artery stenosis are associated with PSD. It was suggested that cerebral artery stenosis was a risk factor of PSD and should be recognized and intervened early.